KOMPONEN KIMIA DAN UJIANTIBAKTERIMINYAK ATSIRIDAUN KI CENGKEH (Urophyllum arboreum (Reinw. ex. Bl.) Korth.) - Praptiwi, Praptiwi; Jamal, Yuliasri; Murningsih, Tri (Research Center for Biology-Indonesian Institute of Sciences, 2002)
This study was done to determine the chemical compounds and antibacterial activity of ki cengkeh (Urophyllum arboreum (Reinw.ex. Bl.) Korth.) essential oil. Ki cengkeh has already known as medicinal plant in some places in Indonesia. This might be correlated with its chemical compounds. The analysis of chemical compounds of ki cengkeh essential oil was done by GC-MS, while antibacterial test was done by paper disc method against 3 bacteria isolates (Staphylococcus aureus, S. epidermidis and Eschericia coli). The result of GC-MS analysis showed that there were 25 compounds with the concentration more than 1% and carryophylen oxide as the highest compound (12.03%). The highest antibacterial activity was found against S. epidermidis.